Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Given the functions:
[tex]\[
\begin{array}{l}
f(x) = 2x - 3 \\
g(x) = 3x - 1
\end{array}
\][/tex]

Find [tex]\((f \cdot g)(x)\)[/tex].

A. [tex]\(6x^2 + 3\)[/tex]

B. [tex]\(6x^2 - 11x + 3\)[/tex]

C. [tex]\(6x^2 - 7x + 3\)[/tex]

D. [tex]\(6x^3 - 11x^2 + 3x\)[/tex]


Sagot :

To find [tex]\((f \cdot g)(x)\)[/tex] given [tex]\(f(x) = 2x - 3\)[/tex] and [tex]\(g(x) = 3x - 1\)[/tex], we need to multiply these two functions together.

Let's go through the multiplication step-by-step:

1. Write down the expressions for [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ f(x) = 2x - 3 \][/tex]
[tex]\[ g(x) = 3x - 1 \][/tex]

2. To find the product [tex]\((f \cdot g)(x)\)[/tex], multiply the expressions for [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ (f \cdot g)(x) = (2x - 3)(3x - 1) \][/tex]

3. Use the distributive property (also known as FOIL method for binomials) to multiply each term in the first polynomial by each term in the second polynomial:
[tex]\[ (2x - 3)(3x - 1) = 2x \cdot 3x + 2x \cdot (-1) + (-3) \cdot 3x + (-3) \cdot (-1) \][/tex]

4. Perform the multiplications:
[tex]\[ 2x \cdot 3x = 6x^2 \][/tex]
[tex]\[ 2x \cdot (-1) = -2x \][/tex]
[tex]\[ (-3) \cdot 3x = -9x \][/tex]
[tex]\[ (-3) \cdot (-1) = 3 \][/tex]

5. Combine all the terms:
[tex]\[ (f \cdot g)(x) = 6x^2 - 2x - 9x + 3 \][/tex]

6. Simplify by combining like terms ([tex]\(-2x\)[/tex] and [tex]\(-9x\)[/tex]):
[tex]\[ (f \cdot g)(x) = 6x^2 - 11x + 3 \][/tex]

Thus, the product of the functions [tex]\(f(x) = 2x - 3\)[/tex] and [tex]\(g(x) = 3x - 1\)[/tex] is:

[tex]\[ (f \cdot g)(x) = 6x^2 - 11x + 3 \][/tex]

The correct choice from the given options is:
[tex]\[ 6x^2 - 11x + 3 \][/tex]